Assessment of fetal cardiac function in early fetal life: feasibility, reproducibility, and early fetal nomogramsAJOG Global Reports at a Glance - Pilar Prats, PhD; M. Teresa Izquierdo, MD; M. Ángeles Rodríguez, PhD; Ignacio Rodríguez, MSc; Alberto Rodríguez-Melcón, MD; Bernat Serra, MD; Gerard Albaiges, MD (Elsevier, 2024)
BACKGROUND: Fetal cardiology has shown a rapid development in the past decades. Fetal echocardiography is not only used for the detection of structural anomalies but also to assess fetal cardiac function. Assessment of the fetal cardiac function is performed mostly in the second and third trimesters. The study of fetal cardiac function at the end of first trimester has not been investigated properly, and there is a lack of reference values at early gestational weeks. OBJECTIVE: This study aimed to assess if the measurement of time-related parameters of cardiac function in the left ventricle of the fetal heart is feasible and reproducible at the end of the first trimester. If possible, we provide nomograms of these parameters from 11 to 13+6 gestational weeks. STUDY DESIGN: We conducted a prospective observational study from March to September 2022. The study was carried out in 2 hospitals (Hospital Universitari Dexeus, Barcelona, and Hospital VITAHS 9 Octubre, Valencia, Spain). The scans were performed by 3 specialists in fetal medicine. The exclusion criteria were fetal cardiac rhythm abnormalities, abnormal nuchal translucency, abnormal ductus venosus, fetal malformations, stillbirth, estimated fetal weight <10 percentile, diabetes, and gestational hypertensive disorders. The cardiac function parameters studied in the left ventricle were isovolumetric contraction time, isovolumetric relaxation time, ejection time, filling time, cycle time, myocardial performance index, ejection time fraction, and filling time fraction. We study the feasibility and intra- and interobserver reproducibility of these parameters using the interclass correlation coefficient. Nomograms were created and the percentiles of the values of the different parameters were calculated. RESULTS: A total of 409 cases were recruited but only 296 could be included in the statistical analysis once the exclusion criteria were applied. The intraobserver reproducibility study was excellent (interclass correlation coefficient >0.900), and the interobserver reproducibility study was good (interclass correlation coefficient >0.700). The data regression analysis showed that cycle time, filling time, isovolumetric contraction time, and filling time fraction increased with gestational age, whereas ejection time fraction decreased with gestational age and myocardial performance index (mean, 0.43±0.08), isovolumetric relaxation time (mean, 0.04±0.01), and ejection time (mean, 0.16±0.01) remained constant from 11 to 13 weeks. CONCLUSION: The study of fetal cardiac function is feasible and reproducible at 11 to 13+6 gestational weeks. Nomograms of the studied parameters are provided.